Martyrdom in the Modern Middle East - Dehghani, Sasha; Horsch, Silvia (Ergon, 2014)
This volume assembles contributions from different academic perspectives (religious and Islamic studies, literary and theatre studies, theology, sociology and history) on modern manifestations of martyrdom in the diverse Middle Eastern religious traditions, including Islam, Christianity, Judaism and the Baha'i-faith. The latter is considered in more detail since it is often not included in comparative studies on the monotheistic religions. An excursus into the farer East composes the contribution on Mahatma Ghandi. The volume considers central sociological, philosophical and theological problems which lie at the heart of the phenomenon of martyrdom, the significance of martyrdom in different conflicts, the competing martyr figures which develop in the course of these conflicts as well as the accompanying representations in art and ritual.